MANAJEMEN PENGGUNAAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DALAM PEMBELAJARAN ASWAJA PADA MADRASAH - Afif, Luthfi (Institut Agama Islam Ngawi, 2024)
The Implementation of Information and Communication Technology (ICT) is crucial to support the learning process, including Aswaja-related learning. This study aims to analyze the application of Information and Communication Technology (ICT) in the teaching of Ahlussunnah wal Jamaah (Aswaja) at MI Wali Aminah Jombang. The study employs a qualitative method with a descriptive approach. Data were obtained through interviews, observations, and document analysis. The results of the study indicate that educators have prepared the learning materials well and have used various ICT facilities, such as videos and presentations, to deliver the material through lecture-based methods. However, the research also identifies some challenges, including the limited understanding of lower-grade students due to some teachers' constraints in utilizing ICT optimally. In conclusion, the implementation of ICT in Aswaja teaching at MI Wali Aminah Jombang has been successful but still requires further improvement. Therefore, IT proficiency is essential to enhance the effectiveness of religious-based Aswaja learning.